Applying the Preview, Question, Read, Summarize, and Test Method to Enhance the Effective Reading Speed of Elementary School Students - Juneli, Juni Artha; Hartati, Tatat; Sopandi, Wahyu; Sujana, Atep (Universitas Pendidikan Indonesia, 2025)
Reading ability is a fundamental skill essential to the learning process. However, a low Effective Reading Speed (ERS), which includes both reading speed and comprehension, poses a significant challenge that can negatively impact student learning outcomes. Slow reading speed and inadequate comprehension hinder students from effectively absorbing information, ultimately affecting their overall academic performance. This study aims to assess the ERS of elementary school students after implementing the Preview, Question, Read, Summarize, Test (PQRST) method in their learning process. It employs a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consists of 20 fifth-grade students selected from a population of 84 at a primary school in Coblong Subdistrict, Bandung City, West Java Province, Indonesia. Data collection involved reading speed and comprehension tests, which were analyzed using the ERS formula. The results indicate that the PQRST method is effective for teaching reading, particularly in improving ERS. Post-test results show a notable improvement compared to pretest scores. This study provides empirical evidence supporting the effectiveness of the PQRST method in elementary education, encouraging teachers to integrate it into their reading instruction. Additionally, it serves as a reference for further research on reading strategies in early education.